Utopias - Adorno, Theodor W.; Allen, Jennifer; Noble, Richard (London : Whitechapel Gallery ; Cambridge, Mass. : MIT Press, 2009)
Joseph Beuys; Paul Chan; Guy Debord; Jeremy Deller; Liam Gillick; Antony Gormley; Dan Graham; Thomas Hirschhorn; Ilya Kabakov; Bodies Isek Kingelez; Paul McCarthy; Constant Nieuwenhuys; Paul Noble; Nils Norman; Philippe Parreno; Pil & Galia Kollectiv; Superflex; Rirkrit Taravanija; Mark Titchner; Atelier van Lieshout; WochenKlausur; Carey Young
Formerly CIP.
boek
Keywords: Art, Modern -- 20th century; Art, Modern -- 21st century; Utopias in art; Art and society -- History -- 20th century; Art and society -- History -- 21st century